PEMBERIAN UPAH BURUH TANI KELAPA SAWIT DI DESA KERITANG KECAMATAN KEMUNING KABUPATEN INDRAGIRI HILIR DALAM PERSPEKTIF EKONOMI SYARIAH - Silvi Handayani; Abd. Malik; Khairiyani (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2023)
The purpose of this study to: (1) find out how the wage system for oil palm farm workers is (2) to determine welfare in the view of Islamic economics (3) to find out whether the given household can meet the needs of oil palm farm workers. This study uses a qualitative method. Methods of collecting data through interviews, observation, and documentation. The population in this study were farm laborers and farmers in the village of Keritang who found 30 people. The results show that the wage system used in Keritang Village uses a piece rate system. Pricing in the view of Islamic economics is in accordance with Islamic principles. However, offering gifts that have not been able to fulfill the eligibility, because the life that has been set has not been able to meet the needs of farm workers. The provision of wages has also not been able to meet the needs of life and has not been able to improve the welfare of the families of the farm workers.